The impact of image acquisition time on registration, delineation and image quality for magnetic resonance guided radiotherapy of prostate cancer patients. (July 2021) - Nowee, Marlies E.; van Pelt, Vivian W.J.; Walraven, Iris; Simões, Rita; Liskamp, Carmen P.; Lambregts, Doenja M.J.; Heijmink, Stijn; Schaake, Eva; van der Heide, Uulke A.; Janssen, Tomas M.
Abstract: Background and Purpose: Magnetic resonance (MR) guided radiotherapy utilizes MR images for (online) plan adaptation and image guidance. The aim of this study was to investigate the impact of variation in MR acquisition time and scan resolution on image quality, interobserver variation in contouring and interobserver variation in registration. Materials and Methods: Nine patients with prostate cancer were included. Four T2-weighted 3D turbo spin echo (T2w 3D TSE) sequences were acquired with different acquisition times and resolutions. Two radiologists assessed image quality, conspicuity of the capsule, peripheral zone and central gland architecture and motion artefacts on a 5 point scale. Images were delineated by two radiation oncologists and interobserver variation was assessed by the 95% Hausdorff distance. Seven observers registered the MR images on the planning CT. Registrations were compared on systematic offset and interobserver variation. Results: Acquisition times ranged between 1.3 and 6.3 min. Overall image quality and capsule definition were significantly worse for the MR sequence with an acquisition time of 1.3 min compared to the other sequences. Median 95% Hausdorff distance showed no significant differences in interobserver variation of contouring. Systematic offset and interobserver variation in registration were small (<1 mm) and of no clinical significance. Conclusions: Our results can be used to effectively shorten overall fraction time for online adaptive MR guided radiotherapy by optimising the imaging sequence used for registration. From the sequences studied, a sequence of 3.1 min with anisotropic voxels of 1.2 × 1.2 × 2.4 mm 3 provided the shortest acquisition time without compromising image quality.